Effect of beta adrenergic blockade on thallium-201 myocardial perfusion imaging. Issue 1 (January 1983) - Hockings, B; Saltissi, S; Croft, D N; Webb-Peploe, M M
Abstract : Nine patients with stable angina (group 1) underwent maximal treadmill stress testing and thallium-201 (201T1) myocardial scintigraphy after intravenous propranolol hydrochloride, and after placebo. Though seven of the nine patients exercised longer after propranolol than after placebo, this difference did not reach statistical significance. Propranolol, however, significantly reduced the mean maximum rate pressure product. Comparison of the perfusion scans on and off propranolol showed that in 36 out of 90 of the myocardial segments recorded (nine patients, five segments scanned twice per patient), only one of the scans showed a defect. In 24 out of 36 of these the propranolol scan was negative, the defect appearing in the placebo scan. Defects present on both scans but differing significantly in size occurred in 22 out of 54 view pairs (nine patients, three views after exercise and three views after redistribution on propranolol and on placebo), and in 19 of these the smaller defect was seen in the propranolol scan. In one of the nine patients, the propranolol scan was normal (false negative), whereas defects corresponding to angiographically proven coronary artery lesions were seen on the placebo scan. Six patients (group 2) were maximally exercised after propranolol and then re-exercised to the same rate pressure product on placebo. Again 16 out of 60 of the segment pairs disagreed and in 10 of these the unmatched defect was present on the placebo scan. In 10 out of 14 discrepant view pairs, the smaller defect occurred on the propranolol scan. Thus in patients taking propranolol, negative results do not exclude coronary artery disease, and perfusion defects (if present) though accurately reflecting the presence of disease may underestimate its true extent.